PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AL-QUR’AN HADIS DI MIS BIRINGERE KABUPATEN BANTAENG - Zulhijrah, Zulhijrah; Muzakkir, Muzakkir; Munirah, Munirah (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2023)
This research is an expost facto quantitative research with a simple linear regression research design, while the research objectives are to describe learning styles and measure learning outcomes and to examine the effect of learning styles on student learning outcomes in al-qur’an hadith subjects at MIS Biringere Bantaeng Regency.The instrument used is a questionnaire in managing data, analyzed using descriptive analysis and inferential analysis. Student learning outcomes in al-Qur’an hadith subjects at MIS Biringere Bantaeng Regency in the medium category learning style has a coefficient value of 0.044, has a t-count value of -1.88 <1.691 t-table, and a significant value of 0.068>0.05. This means that the learning style variable does not have a positive and significant effect on learning outcomes. Prove that H0 is accepted and Hα is rejected. And the contribution of the influence of learning styles on student learning outcomes in al- Qur’an hadith subjects is 0.026% while the rest is influenced by other variables.